Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda) - Sousa, Francisco Diogo R.; Elmoor-Loureiro, Lourdes M. A. (Zootaxa, 2018)
In this study, we investigated cladocerans (Crustacea: Branchiopoda) collected in six water bodies from the Upper Xingu River Basin, Central Brazil. In total, we found eighteen species belonging to three families. Furthermore, we also describe a new and highly specialized genus of Chydoridae. Kisakiellus aweti gen. nov., sp. nov. which shares some morphological traits with members of Chydorinae, particularly the exopodite of the fourth limb armed with seven setae. The new genus bears several autapomorphies and does not exhibit any clear affinities with any other genus of the subfamily. Apparently, K. aweti gen. nov., sp. nov. has a positive rheotactic behavior and the morphological characters related to this habitat trait are discussed. Many regions of the Upper Xingu River Basin are still in need of faunal inventories, a fact that gains more relevance due to the high potential for cryptic biodiversity. So, it is possible that an increase on the sampling effort in this basin will have a positive impact on the known diversity of Cladocera.